Anatomia de órgãos vegetativos e escapo de Rondonanthus (Eriocaulaceae - Poales) - Oliveira, Fernanda Martins Gonzaga de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Eriocaulaceae is a pantropical family and comprises ten genera. Rondonanthus is endemic to the north region of South America and comprises six species. The anatomy of roots, stem, leaves and scapes were studied in four species to characterize the genus and to identify characteristics with taxonomic value. The following characteristics are diagnostic of Rondonanthus: roots - heterogeneous cortex with an aerenchyma supported by arm cells and vascular cylinder with a central metaxylem vessel element; stems - idioblasts with druses in the cortex and in the pith; leaves - Malpighian hairs, hypodermis in the adaxial surface, chlorenchyma with arm cells, druse idioblasts in the mesophyll, and vascular bundle sheath extensions with rounded cells; scapes - Malpighian hairs and chlorenchyma with arm cells. Rondonanthus capillaceus differed from the remaining species studied by presenting roots with a homogeneous cortex with thin-walled cells; filiform leaves without stomata and trichomes but with a chlorophyllous epidermis and a parenchymatous mesophyll and only one central vascular bundle without sheath extensions. Such differences may be related to the habitat, since this species grows on rivers' margins and requires hydrodynamic organs. The number of vascular bundles in the leaves is a useful characteristic to differentiate among the species

Eriocaulaceae é uma família pantropical e compreende dez gêneros. Rondonanthus é endêmico da região norte da América do Sul e inclui seis espécies. Foi estudada a anatomia de raízes, caules, folhas e escapos de quatro espécies, buscando-se identificar características com valor taxonômico. As seguintes características são diagnósticas de Rondonanthus: raízes - córtex heterogêneo com aerênquima sustentado por células braciformes e cilindro vascular com um único elemento de vaso de metaxilema ocupando posição central; caules - idioblastos com drusas no córtex e na medula; folhas - tricomas malpighianos, hipoderme na face adaxial, clorênquima com células braciformes, idioblastos com drusas no mesofilo e extensões de bainha de feixe vascular com células arredondadas; escapos - tricomas malpighianos e parênquima clorofiliano com células braciformes. Rondonanthus capillaceus se diferencia das demais espécies estudadas por apresentar raízes com córtex homogêneo com células de paredes finas; folhas filiformes sem estômatos e tricomas, com epiderme clorofiliana, mesofilo parenquimático, e apenas um feixe vascular central sem extensões de bainha. Tais diferenças podem estar relacionadas com o habitat, já que esta espécie cresce nas margens de rios e necessita de órgãos hidrodinâmicos. O número de feixes vasculares nas folhas é uma característica útil para diferenciar as espécies de Rondonanthus
Keywords: Anatomia vegetal; Raizes (Botanica); Caules de planta; Folhas - Anatomia; Plant anatomy